Monoclonal B-cell lymphocytosis and prostate cancer: Incidence and effects of radiotherapy. (April 2019) - D'Auria, Fiorella; Valvano, Luciana; Rago, Luciana; Statuto, Teodora; Calice, Giovanni; D'Arena, Giovanni; Fusco, Vincenzo; Musto, Pellegrino
Monoclonal B-cells lymphocytosis (MBL) is a benign condition that may precede chronic lymphocytic leukemia (CLL), not rarely present in peripheral blood of healthy elderly people, among which there is also a male prevalence. Though CLL has been associated with various types of solid tumors, including prostate cancer (PC), no data exist about the relationship between PC and MBL. We studied the frequency of CLL-like MBL clones in a group of 48 patients affected by PC and followed them during and after whole-pelvis radiotherapy (WPRT) treatment. We found four MBL clones (8.3%), two of which (4.2%) had a B-cell clonal count >1000 cells/µL ('clinical MBL'). A single case (1.8%) of 'low-count' MBL occurred in a control group of 54 healthy males. Notably, normal B-lymphocytes were consistently affected by WPRT, while MBL clones were less radiosensitive. Our results suggest a possible association between 'clinical' MBL and PC and show a different impact of the radiation on monoclonal respect to normal B-cells, which could also imply a greater risk of clonal transformation.